2008
DOI: 10.1007/s11103-008-9290-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide allele-specific expression analysis using Massively Parallel Signature Sequencing (MPSS™) Reveals cis- and trans-effects on gene expression in maize hybrid meristem tissue

Abstract: Allelic differences in expression are important genetic factors contributing to quantitative trait variation in various organisms. However, the extent of genome-wide allele-specific expression by different modes of gene regulation has not been well characterized in plants. In this study we developed a new methodology for allele-specific expression analysis by applying Massively Parallel Signature Sequencing (MPSS), an open ended and sequencing based mRNA profiling technology. This methodology enabled a genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 53 publications
(83 reference statements)
4
69
0
Order By: Relevance
“…It has been suggested that nonadditive variation is generally controlled by trans-acting factors, whereas 28 The Plant Cell additive variation could result from both cis-and trans-acting effects (Swanson-Wagner et al, 2006;Springer and Stupar, 2007;Guo et al, 2008). In our study, significantly more genes exhibited nonadditive than additive expression patterns in both reciprocal hybrids ( Figure 4B; see Supplemental Figure 12 online), suggesting predominantly trans-acting effects in the transcriptional diversity of these genes in hybrids.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It has been suggested that nonadditive variation is generally controlled by trans-acting factors, whereas 28 The Plant Cell additive variation could result from both cis-and trans-acting effects (Swanson-Wagner et al, 2006;Springer and Stupar, 2007;Guo et al, 2008). In our study, significantly more genes exhibited nonadditive than additive expression patterns in both reciprocal hybrids ( Figure 4B; see Supplemental Figure 12 online), suggesting predominantly trans-acting effects in the transcriptional diversity of these genes in hybrids.…”
Section: Discussionmentioning
confidence: 48%
“…Following previous reports (Mikkelsen et al, 2007;Guo et al, 2008), we also investigated whether an allelic bias in gene expression or epigenetic modifications was present in hybrids. The patterns uncovered here were clear and showed an allelic bias that exhibited the same direction between reciprocal hybrids and a positive correlation with differences between parents.…”
Section: Discussionmentioning
confidence: 94%
“…This approach has been exploited to great effect in model systems where constructing inbred parental lines and their F 1 hybrid is easily done. This approach has been applied both between individuals from within the same species in maize (Stupar & Springer 2006;Springer & Stupar 2007a,b;Stupar et al 2007Stupar et al , 2008Guo et al 2008) (ii) The F 1 hybrids are crossed through random mating for N generations to produce F N hybrids. (iii) The F N hybrids are subjected to a method of isogenization, whereby all, or nearly all, of the genome is made homozygous.…”
Section: Allele-specific Assays For Measuring Cis and Trans Expressiomentioning
confidence: 99%
“…In eQTL mapping studies the characterization of cis-and trans-genetic variation depends on positional cutoff and an unambiguous separation of true cis and trans effect is impossible (Ronald et al 2005b). An alternative approach detects cis-regulatory variation by direct testing of allele-specific expression (ASE) in a heterozygous system (Cowles et al 2002;Yan et al 2002;Lo et al 2003;Wittkopp et al 2004;de Meaux et al 2006; Kiekens et al 2006;Springer and Stupar 2007;Guo et al 2008). The existence of trans-genetic variation is revealed by testing for a deviation between hybrid allelic expression and a mix of the parental expression profiles (Wittkopp et al 2004;Springer and Stupar 2007;Guo et al 2008).…”
mentioning
confidence: 99%
“…An alternative approach detects cis-regulatory variation by direct testing of allele-specific expression (ASE) in a heterozygous system (Cowles et al 2002;Yan et al 2002;Lo et al 2003;Wittkopp et al 2004;de Meaux et al 2006; Kiekens et al 2006;Springer and Stupar 2007;Guo et al 2008). The existence of trans-genetic variation is revealed by testing for a deviation between hybrid allelic expression and a mix of the parental expression profiles (Wittkopp et al 2004;Springer and Stupar 2007;Guo et al 2008). Since parental genotypes vary for both cis and trans effect, comparison of parental expression variation with the hybrid cis effect highlights loci regulated by ''composite'' trans difference, e.g., multiple trans eQTL, developmental and environmental dependency, and cis 3 trans interaction.…”
mentioning
confidence: 99%